and Antimalarial Activities and Toxicological Assessment of (Blanco) Benth - Arisara Phuwajaroanpong BSc; Prapaporn Chaniad PhD; Natharinee Horata PhD; Saowanee Muangchanburee MSc; Kantarakorn Kaewdana BSc; Chuchard Punsawad PhD (SAGE Publishing, 2020)
The aim of this study was to investigate the antimalarial activities and toxicity of Pogostemon cablin extracts. In vitro activities against the chloroquine-resistant Plasmodium falciparum K1 strain were assessed by using the Plasmodium lactate dehydrogenase enzyme (pLDH) assay, while in vivo activity against the Plasmodium berghei ANKA strain in mice was investigated using a 4-day suppressive test. The in vitro and in vivo toxicity were determined in Vero cells and mice, respectively. The ethanolic extract possessed antimalarial activity with an IC 50 of 24.49 ± 0.01 µg/ml, whereas the aqueous extract showed an IC 50 of 549.30 ± 0.07 µg/ml. Cytotoxic analyses of the ethanolic and aqueous extracts revealed a nontoxic effect on Vero cells at a concentration of 80 µg/ml. Based on a preliminary study of in vitro antimalarial activity, the ethanolic extract was chosen as a potential agent for further in vivo antimalarial activity analysis in mice. The ethanolic extract, which showed no toxic effect on mice at a dose of 2000 mg/kg body weight, significantly suppressed parasitemia in mice by 38.41%, 45.12% and 89.00% at doses of 200, 400 and 600 mg/kg body weight, respectively. In conclusion, this study shows that the ethanolic P. cablin extract possesses in vitro and in vivo antimalarial activity without toxic effects.